Optimasi Variasi Menu Makanan Sesuai Gizi Pada Anak Panti Asuhan Dengan Improved Particle Swarm Optimization - Aldino Caturrahmanto; Lailil Muflikhah; Imam Cholissodin (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Nutrition is a compound which important to human growth and their health. Nutrition consumption is really important that they can affect health if poorly managed. Unfortunately, there are still places which have poorly managed nutrition planning, which one of them is Orphanage. Improved Particle Swarm Optimization is an Evolutionary Algorithm which is based on nature folks of birds flying in group searching for new food points. This Algorithm have great ability to search local optimum solution and also global optimum solution. In this case, a list of foods menu will be represented by a Particles which consisting indexes of number represent menu. The result of our testing found that swarm size of 70 and combination of 2,0 for C1 and C2 is the best parameter for this problem. Although giving great solution based on Nutrition, this algorithm still offer total price above our limit value.